Production of recombinant lethal factor of Bacillus anthracis in Bacillus subtilis. Issue 1 (2nd January 2021) - Gholami, Mahboobeh; Moghbeli, Majid; Kafilzadeh, Farshid; Kargar, Mohammad; Torbati, Mariam Bikhof; Tavizi, Ashkan; Bellevile, Sally; Hatami, Javad; Eslami, Zahra
Abstract: Cancer is considered as a disease with high rates of mortality and morbidity. The limitations and side effects of common treatments have prompted the need for innovative cancer therapies. Furthermore, selectivity and targeting of cancer cells are crucial factors to successful treatment of cancer. One of these methods is the use of bacterial toxins including Bacillus anthracis toxin to aid cancer therapy. This toxin is composed of three polypeptides: protective factor (PA), lethal factor (LF), and edema factor (EF). PA can bind to various surface receptors of all types of human cells and it internalizes the lethal factor and edema factor subunits of the toxin in the cytosol. In the present study, we cloned and expressed the lef gene of B. anthracis as the lethal part of the toxin in Bacillus subtilis WB600 by a shuttle expression vector PHT4. The rLF made in B. subtilis is efficiently secreted by the host into the culture medium which facilitates downstream processing. The rLF can be used to study cancer treatment. Abbreviations: EF: edema factor; LF: lethal factor; PA: protective factor; rLF: recombinant lethal factor; rPAm: recombinant protective factor mutants; uPA: urokinase-type plasminogen activator; uPAR: urokinase-type plasminogen activator receptor.